Determinação de elementos potencialmente tóxicos em amostras de solo utilizando extração assistida por ultrassom e espectrometria de absorção atômica - Silva, Deborah Cristina Crominski da (2018)
This study proposed a simple and effective method for determination of total As, Al, Cd, Cu, Ni and Zn in soil samples, associating ultrasound-assisted extraction and atomic absorption spectrometry (HG-AAS and FAAS). The factorial design was applied to determine the hydride generation conditions for total As determination, which concluded that the application of 0.36% m v-1 NaBH4 in 0.05% m v-1 NaOH as reducing agent and 10% v v-1 HCl as carrier agent greatly improved the absorbance obtained for total As determination in HG-AAS. Ultrasound-assisted extraction was applied to determine potentially toxic elements in soil samples. Parameters of acids concentration in extraction solvent and extraction time were evaluated using a central composite design to establish the best conditions. 0.1 g of soil sample in 2 mL containing 3.00, 3.60 and 2.78 mol L-1 of HCl, HNO3 and HF, respectively, at 60 min of extraction time were determined as optimal conditions for determination of Al, Cd, Cu, Ni and Zn. Total As was determined using 0.1 g of soil sample in 2 mL of 12.08 mol L-1 HCl. Method accuracy was determined by analysis of certified soil samples BCR-142, Clay Soil 1, RM-Agro E2002a and RS-3 with Student t-test at 95% confidence level. Detection limites were 0.23 mg g-1 for Al and 0.25, 1.30, 1.61, 1.77 and 7.39 µg g-1 for total As, Zn, Cd, Cu e Ni, respectively. Ultrasoundassisted proved to be a simple and straightforward pretreatment technique to determine the concentrations of total total As, Al, Cd, Cu, Ni and Zi in soil samples. Eight sites characterized as agricultural and native forest areas of Ponta Grossa and Guarapuava cities, Parana State, Brazil were assessed for the studied elements by comparison to the reference values for trace elements provided by the Brazilian National Environment Council, concluding that the native forest areas of sites 2, 5, 6 e 7 and 3, 4 e 8 present soils of native forest with levels of total As and Cu, respectively, above the limits considered of prevention. None of the sites were above the agricultural area limit. In addition, geoaccumulation index, enrichment and contamination factors, and pollution load index were calculated for soils from agricultural areas in order to determine the degree of the contribution from anthropogenic sources for metal concentrations, which concluded that all sites were unpolluted to moderately polluted and none or minor enrichment due to antropogenic activities were noticed.